Fluid management in patients with trauma: Restrictive versus liberal approach - Veena Chatrath; Ranjana Khetarpal; Jogesh Ahuja (Wolters Kluwer Medknow Publications, 2015)
Trauma is a leading cause of death worldwide, and almost 30% of trauma deaths are due to blood loss. A number of concerns have been raised regarding the advisability of the classic principles of aggressive crystalloid resuscitation in traumatic hemorrhagic shock. Some recent studies have shown that early volume restoration in certain types of trauma before definite hemostasis may result in accelerated blood loss, hypothermia, and dilutional coagulopathy. This review discusses the advances and changes in protocols in fluid resuscitation and blood transfusion for treatment of traumatic hemorrhage shock. The concept of low volume fluid resuscitation also known as permissive hypotension avoids the adverse effects of early aggressive resuscitation while maintaining a level of tissue perfusion that although lower than normal, is adequate for short periods. Permissive hypotension is part of the damage control resuscitation strategy, which targets the conditions that exacerbate hemorrhage. The elements of this strategy are permissive hypotension, minimization of crystalloid resuscitation, control of hypothermia, prevention of acidosis, and early use of blood products to minimize coagulopathy.